2019
DOI: 10.22159/ajpcr.2019.v12i1.30369
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and Dissolution Enhancement of Ivacaftor Tablets by Using Solid Dispersion Technique of Hot-Melt Extrusion - A Design of Experimental Approach

Abstract: Objective: The objective was to improve the solubility and dissolution of ivacaftor tablets by using solid dispersion (SD) technique.Methods: Ivacaftor is practically insoluble (<0.001 mg/mL) over pH value of 3.0–7.5 due to low solubility, and it shows poor bioavailability after oral administration. Therefore, SDs of Ivacaftor were prepared by SD technique of hot-melt extrusion (HME) by adding different polymers such as Soluplus, Hypromellose 5 cps, and Copovidone with surfactants sodium lauryl sulfate, pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The extensive literature survey on LDV and SBV indicated that there was only one research work was published regarding the development of fast disintegrating tablets of LDV only [12]. This indicates that there is a large scope for performing research on this newly approved fixed dose combination drugs towards improving their bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…The extensive literature survey on LDV and SBV indicated that there was only one research work was published regarding the development of fast disintegrating tablets of LDV only [12]. This indicates that there is a large scope for performing research on this newly approved fixed dose combination drugs towards improving their bioavailability.…”
Section: Introductionmentioning
confidence: 99%